2014
DOI: 10.1007/s40732-014-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collateral Response Requirements and Exemplar Training on Listener Training Outcomes in Children

Abstract: We evaluated the effects of collateral response requirements during listener training on the emergence of vocal foreign-language tacts and intraverbals among 4-and 5-yearold children. In Experiment 1, participants were first exposed to auditory-visual match-to-sample training without collateral response requirements. Four participants did not perform to criterion in probes for derived vocal responses, and were exposed to a two-phase intervention that involved adding echoic and native-language tact requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
(39 reference statements)
1
15
0
3
Order By: Relevance
“…Potential implications for the role of echoic responding should be tempered in light of the issues described previously, as each of the three experiments had its own strengths and limitations. However, they fail to provide support for the notion that echoic responses during pairing are crucial to later tact emergence (Horne & Lowe, 1996), and as such, they are consistent with the results of other studies that have attempted to document this functional role (Byrne et al, 2014;Carp et al, 2015;Delfs et al, 2014;Haq et al, 2017;Olaff & Holth, 2020;Petursdottir et al, 2014). Anecdotally, some of the incorrect responses of our participants also seem to contradict this role of echoic responding.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Potential implications for the role of echoic responding should be tempered in light of the issues described previously, as each of the three experiments had its own strengths and limitations. However, they fail to provide support for the notion that echoic responses during pairing are crucial to later tact emergence (Horne & Lowe, 1996), and as such, they are consistent with the results of other studies that have attempted to document this functional role (Byrne et al, 2014;Carp et al, 2015;Delfs et al, 2014;Haq et al, 2017;Olaff & Holth, 2020;Petursdottir et al, 2014). Anecdotally, some of the incorrect responses of our participants also seem to contradict this role of echoic responding.…”
Section: Discussionsupporting
confidence: 64%
“…First, the effects of requiring echoic responses during stimulus pairing or listener instruction should be evaluated further, incorporating control conditions that attempt to interfere with or block echoic responses. The occurrence of echoic responses at the covert level when they were not required may explain the negative results of previous studies that have evaluated echoic response requirements (e.g., Petursdottir et al, 2014), and interfering with that behavior could potentially reveal an effect. A recent study (Dressel, Nicholson, Albert, & Ryan, 2019) found that blocking echoic responses during stimulus pairing did not interfere with emergent intraverbal control in an instructive feedback procedure; however, no similar research has been published on emergent tact control.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Neither study found a consistent relationship between collateral responding and emergence. Studies excluded from this review, such as Petursdottir, Lepper, and Peterson (), found that requiring collateral echoic responding during listener training did not result in emergence of speaker responses. Thus, we recommend that researchers begin to look beyond collateral responding as a variable supporting emergence.…”
Section: Resultsmentioning
confidence: 99%
“…During listener categorization training trials, it may be more effective to train the pointing response, and the autoclitic frame BStimulus is Category.^For example, the experimenter would provide the discriminative stimulus, BWhich one is Africa?^and then train the participant to point to BDurbin,^then vocalize the statement BDurbin is Africa.^Although previous research has indicated that echoic, multiple-tact, and receptive discrimination training does not significantly influence the emission of intraverbal behavior (Miguel et al 2005;Petursdottir et al 2014), perhaps embedding this training as an autoclitic frame in an alternating format with intraverbal categorization trials in the context of MEI may teach the child to emit relevant responses that would generate stimulus control over categorization responding and result in emergent intraverbal categorization.…”
Section: Discussionmentioning
confidence: 99%